Comunicação sem reservas: ensaios de malandragem e preguiça - Costa, Edil Silva (2005)
This work stars from a corpus of popular stories collected in the João Preguiçoso and Pedro Malasartes´s cycle chosen in the State of Bahia. It approaches the strength and consistent themes as the cunning and laziness which persists inside Brazilian culture. These themes follow principles identities that make them stronger. Not only looking forward contributing to studies of oral tradiction, describing the mechanisms of text production, but also more widely observing the Brazilian culture. The theorical basis of this thesis was built beginning by on one side in Paul Zumthor and Jerusa Pires Ferreira´s writings, and also cultural semiotics in Iuri Lotman. On the other hand, we also read cultural anthropologists works as in Roberto DaMatta, Georges Balandier´s and François Laplantine´s. Otherwise, it was based in cultural studies in Stuart Hall and Homi Bhabha also, elements of communication theories as in Muniz Sodré and Lucrécia D Aléssio Ferrara and others. This thesis is compounded by three issues: The lazyness and the cunning: myths and stereotypes in Brazilian culture . It makes a historical approach, presenting the very beginner texts and the stereotyped built in narratives from colonial times. They were related to utopic literature and also to the medieval imaginary brought to América. In the Oral and the mestice of races , cultural identities and identification ways that comes from the communication processes of popular literature (statements and stories), as expression of civilizatory destinations originaly based on mixed process, underlining afro-brasilian culture. In For a cunning hero tipology , it tracks a panoramic view of the more common cunning types, pointing out and characterizing the cunnings, the fools and also lazy ones, all from popular stories in their relations with others cultural texts, from cartoons to written literature.